THE TEACHING METHODS OF ENGLISH SKILLS - Kasimova Guljakhon Mahmudovna; Ismonova Tursunoy Zokirjonovna (Galaxy International Interdisciplinary Research Journal, 2022)
Language learning is a modern requirement. Many people see language learning as a way to achieve a mature goal. Because a person who knows a language organizes not only the language of that nation, but also its way of life and customs. Organizing it broadens the student's worldview. The more languages ​​we know, the higher our standing among the masses. This article provides information about the ways of IELTS teaching and it`s results. By the help of this article, we want to proof that from A1 beginner students can get over 6 band score during a year. All information in this article is practiced in 2021 and faced to great result.